High-intensity running and sprint distance prior to hamstring injury in elite male soccer players. Is there a common theme in over- or under- loading in the weeks preceding hamstring injury? - Morgans, R.; Oliveira, R.; Ceylan, H. I.; Teixeira, J.; Ryan, B.; Modric, T.; Moreira, A. (Journal of Physical Education and Sport, 2025)
The analysis of the period prior to injury is still scarce in soccer. Thus, the aim of this study was to examine the loading patterns of high-intensity running and sprint distances during the weekly cycle durations across a five- year period in an elite soccer club. Specifically, to investigate any over- or under-loading in the weeks preceding hamstring injury. Thirty professional outfield soccer players from an English Premier League club were involved (age 24.2 ± 6.1 years, weight 74.7 ± 7.8 kg, height 1.81 ± 0.09 m). Injury surveillance, training and match data from the complete 2020/21 season was considered for analysis. Physical data were consistently monitored across the study seasons during all training sessions and matches using an 18Hz Global Positioning System (GPS) technology tracking system. The relative and absolute measures of total distance, high-intensity distance (m; total distance covered 5.5 - 7m/s) and sprint distance (m; total distance covered > 7m/s) were collected. These measures were analyzed considering the four weeks preceding injury (-4, -3, -2, -1) between injured and uninjured players. The main findings revealed that sprint distance per minute was higher in injured than uninjured players in the week preceding the injury (week -1, p = 0.038; ES = -0.89). No other meaningful differences were found. This study highlighted the influence of sprint distance per minute performed in the week preceding injury in elite English Premier League soccer players. Such findings highlight the importance of longitudinal measurements specifically related to sprint distance, while the analysis of two-, three- and four- weeks prior to injury does not seem to add any significant value. Finally, the data from the present study highlights the importance of analyzing relativized data (per minute) compared to absolute data.